92 Eligibility and reimbursement of SGLT2 inhibitors in a heart failure outpatient cohort. (8th December 2021) - Tarantini, Roberto; Vecchi, Andrea Lorenzo; Matteo, Federica; Guerci, Marco; Ponti, Roberto De
Abstract: Aims: In patients affected by heart failure with reduced (HFrEF) and preserved (HFpEF) ejection fraction, sodium–glucose cotransporter type 2 inhibitor drugs (SGLT2i) have shown unexpected and extraordinary results, regardless of the co-presence of diabetes mellitus (DM). The results of the clinical trials have recently allowed the national drug agency (AIFA) to summarize and simplify SGLT2i indications for treatment; however, the reimbursement of these drugs is currently only ensured to diabetic patients, who represent a small subgroup of heart failure (HF) population. The study aims to determine eligibility for SGLT2i in HF outpatients, according to the inclusion criteria of the main clinical trials, comparing the drug label proposed by EMA/AIFA with the current reimbursement criteria. Methods and results: In this retrospective, observational study, 206 HF outpatients were enrolled from September 2018 to September 2019. The percentages of eligible patients according to the DECLARE-TIMI 58, EMPA-REG OUTCOME, DAPA-HF, EMPEROR REDUCED, and EMPEROR PRESERVED inclusion criteria were analysed, comparing the indications proposed by the EMA/AIFA label and the current reimbursement criteria. Among the 206 patients enrolled, the mean age was 71 ± 12 years, 24% were diabetic, the mean MDRD eGFR was 61 ± 22 ml/min/1.73m 2, the mean ejection fraction (LVEF) was 38 ± 11% (LVEF <40 in 65% of the whole cohort). According to EMA/AIFA indications, eligible patients for SGLT2i in this cohort are 66%, representing almost the entire HFrEF population. This percentage, which is far higher than the eligibility of the main clinical trials, is motivated by the more stringent inclusion criteria proposed by the latter, in which the prevailing limiting factors were NYHA class and NTproBNP values. The reimbursement of these drugs is currently only ensured for diabetic patients with eGFR > 60 ml/min/1.73 m 2 ; in our study only 8% of patients met these criteria. Assuming soon to extend the EMA/AIFA indication to HFpEF patients, wider eligibility for SGLT2i is expected for most patients with HF, irrespective of DM and LVEF. Conclusions: Two-thirds of our HF population is currently eligible for SGLT2i prescription, according to the drug label proposed by EMA/AIFA; this eligible cohort includes almost all HFrEF patients. When the indications will be updated according to the results of HFpEF trials on SGLT2i, eligibility will be extended almost to the entire cohort of HF outpatients. Most eligible patients are not diabetic, however, they have not currently access to drug reimbursement. The constant updating of the SGLT2i label and reimbursement criteria is the main limiting factor in current clinical practice.